Diagnostic and therapeutic conduct in vascular wounds - Gateño, Nisso; Torterolo, Edgardo (Cirugía del Uruguay, 1974)
In considering vascular wounds, the author summarizes anatomoclinical characteristics of middle neck and insists on the need of going beyond anatomical limits in order to reach vascular and aerodigestive lesions. Both clinical and paraclinical aspects are discussed, stressing the importance of arteriography. Other aspects include surgical opportunity. approach, duration of clamping and counterindications to repair. Emphasis is laid on the need to resect arterial borders in wounds caused by firearms.